The Formation of Rice Tillers and Factors Influencing It - Rong Yuan; Yuxin Mao; Dehai Zhang; Shun Wang; Huina Zhang; Meng Wu; Miao Ye; Zujian Zhang (Agronomy)
The number of effective rice tillers determines the number of effective panicles and then affects the final yield. Rice tillering ability shows great differences among cultivars and under different environmental conditions, but the underlying mechanisms are not clear. The present paper investigated the formation of rice tillers and examined its genetic regulation, the effects of plant hormones, several environmental factors affecting rice tillering, and nitrogen’s regulation of tillers. Finally, the utilization of the tillering ability of weedy and wild rice was investigated. We concluded that many genes are involved in manipulating rice tillering, including MOC1, MOC3, FON1, LAX1, LAX2, APC/CTE, D3, D10, D14, D17, D27, and D53, by altering associated hormone contents or coding signal substances. The plant hormones auxin (IAA), gibberellin (GA), and strigolactone (SL) inhibit rice tillering, while cytokinin (CTK) promotes rice tillering. Weak light (light intensity is lower than 200 μmol m−2 s−1) and low and high temperatures (below 15 °C and above 38 °C) inhibit rice tillering, while optimized water management, such as alternate wetting and moderate drying irrigation, can greatly promote rice tillering. In addition, increasing plant nitrogen concentration can effectively improve rice tillers by adjusting multiple nitrogen metabolism enzymes. Weedy rice and some wild rice showed obvious superiority in tillering ability with respect to cultivated rice, but the underlying mechanisms are not clear and should be further explored. This study can provide theoretical guidance for the breeding and cultivation of high-yield and high-efficiency rice cultivars.